CHINA-RUSSIA COMPETITION IN CENTRAL ASIA: CURRENT STATUS AND PROSPECTS (Вісник: Міжнародні відносини, 2025)
Abstract The article examines the transformation of competition between the Russian Federation and the People’s Republic of China in Central Asia after 2022. The analysis covers six interconnected domains: security, economic, energy, logistics, migration, and technology. Findings show that Russia maintains the role of security guarantor, while China strengthens its economic and technological presence, forming an asymmetric duumvirate. Special emphasis is placed on the impact of Western sanctions on Russia, the expansion of Chinese energy and transport projects, and the emergence of dual technological dependency among Central Asian states. The study concludes that Kazakhstan’s and Uzbekistan’s multi-vector strategies, along with engagement of the US, EU, and Turkey, can limit the monopolistic ambitions of major powers. For Ukraine, opportunities arise to participate in the Trans-Caspian International Transport Route, expand agricultural and IT exports, and promote the C5+UA diplomatic format.
Keywords: Central Asia; Russian Federation; People’s Republic of China; geopolitical competition; security fragmentation; energy corridors; digital sovereignty.